THE EFFECT OF RED APPLE (Pyrus Malus) TO BLOOD PRESSURE OF GRADE ONE HYPERTENSIVE PATIENTS - Soputri, Nilawati (Journal of International Scholars Conference - ALLIED HEALTH, 2016)
Red Apple (pyrus malus) is a fruit that can be used as a diet approach to stop hypertension due to its potassium and flavonoid content. These content in the red apple can lower blood pressure and inhibit the production of renin that influences the production of angiotensin and angiontensin-converting enzyme. This study aims to seek the beneficial effects of red apples on the blood pressure of Grade I Hypertension patients. The method of the study is quasi experimental with one group pretest post test design. The 15 participants were given 150 grams of red apple for 10 consecutive days. The blood pressure of each patents were taken everyday to monitor on which day there is a change on the blood pressure compared to the first day before consuming the red apple. The data were analyzed with paired sample t-test. The results show that there is a significant change in blood pressure, from an average of 143.7/94.2 mmHg before consuming the red apple to 129/89.4 mmHg after 10 days of consumption. The blood pressure, both systole and diastole, showed significant changes after the first day of consuming the red apple.